A model based on Game theory to measure the effect of sustainable development variables - Zadjabbari, Behrang; Wongthongtham, Pornpit; Dillon, Tharam S (SDSE, 2009)
Sustainable development is becoming one of the main challenges in human development. The notion of coordinating actions between economy, society and environment in order to optimise sustainability of ecosystems is the aim of this paper. Traditionally, relations between economy, society and the environment are win-lose relations; however, to achieve sustainable development they should change to win-win relations. In this paper, we propose a game-theory approach to show the lack of balance between the parts of sustainable development. We present a mathematical model in order to change uncooperative behaviour. Ontology, a particular type of knowledge based technology, is used to define the variables affected on the relations. Ontology helps to understand how those variables affect an economy, society and environment. Generally speaking, ontology is used to explicitly express how sustainable variables are defined in economy, society and environment. Due to the qualitative entity of some of the variables, fuzzy logic is used to measure the variables and TOPSIS methodology is anticipated as a methodology to find optimum answers. It is a suitable way to predict the effect of some solutions, such as emission trading, on the environment, and society as well as the economy. The sensitivity of changes in variables can be analysed. We propose a methodology on the basis of the Game theory to measure sustainability and effects of changing each variable in the relations between sustainable development actors to other variables.